2012
DOI: 10.1039/c2em30084b
|View full text |Cite
|
Sign up to set email alerts
|

Lead traceability along soil-melliferous flora-bee family-apiary products chain

Abstract: Indirect measures were considered to study the lead transfer along the soil-melliferous flora-bee family-apiary products food chain. The concentrations of total and bioavailable lead in the soil were first investigated. Next, the lead level in different organs of melliferous flora and subsequently in the bee family and apiary products was measured. The results indicate a decrease in contamination as follows: honeybees > drones > propolis > wax > bee larvae > honey > royal jelly. The statistical analysis highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Tuzen et al (2007) suggested the use of honey, while according to Bogdanov, Haldimann, Luginbuhl, and Gallmann (2007), low TE concentrations and high natural variations should deter from using honey. In the case of Pb recent studies also showed that honey was the least affected matrix from beehives, but could nonetheless be used for environmental monitoring (Lambert, et al, 2012;Mihaly Cozmuta, Bretan, Mihaly Cozmuta, Nicula, & Peter, 2012). In spite of abundant data from the literature, reference levels for noxious TE in honey are difficult to find (Devillers et al, 2002), and additional data on the potential impacts of a heavily contaminated environ-ment on honey could improve insights and provide additional material to assess the potential risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuzen et al (2007) suggested the use of honey, while according to Bogdanov, Haldimann, Luginbuhl, and Gallmann (2007), low TE concentrations and high natural variations should deter from using honey. In the case of Pb recent studies also showed that honey was the least affected matrix from beehives, but could nonetheless be used for environmental monitoring (Lambert, et al, 2012;Mihaly Cozmuta, Bretan, Mihaly Cozmuta, Nicula, & Peter, 2012). In spite of abundant data from the literature, reference levels for noxious TE in honey are difficult to find (Devillers et al, 2002), and additional data on the potential impacts of a heavily contaminated environ-ment on honey could improve insights and provide additional material to assess the potential risks.…”
Section: Introductionmentioning
confidence: 99%
“…High TE levels in fish have been reported in a similar context elsewhere in the region (Monna et al, 2011), but to date no studies have been conducted on apiary products in the area. As positive relationships regarding Pb traceability were validated along the soil-melliferous flora-honeybees-honey chain (Mihaly Cozmuta et al, 2012), such a study was necessary to assess honey quality from a heavily contaminated area.…”
Section: Introductionmentioning
confidence: 99%
“…A study performed between April and September 2009 on two different zones in Romania investigated the results of translocation from the soil to different apiary products in 15 plants with melliferous potential. It was shown that the plants acted as bioaccumulators, and that contamination decreases as follows: honeybees > drones > propolis > wax > bee larvae > honey > royal jelly [ 49 ]. The authors indicated that the translocation impacts upon the safety and quality of food.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, studies on the use of honeybees and bee products for environmental monitoring have a relatively long history, dating back to at least 1935 (Crane, 1984). Environmental pollutants included in these s tudies were, among others, heavy metals, w hich the bees may take up from all environmental compartments: vegetation, soil, air and water (Bromenshenk et al, 1985;Conti & Botré, 2001;Leita et al, 1996;Mihaly et al, 2012;Porrini et al, 2013). A recent study by van der a ) indicated that adult honeybees can serve to detect temporal and spatial patterns in environmental concentrations of a w ide range of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…We considered that bees w ould be a reliable alternative in case the metal concentrations found in bees and in air would positively co rrelate, and w hen possible significant differences in concentration between locations w ould be similar for bees and air. In contrast to Balestra et al (1992) who studied honey, pollen and bee larvae, we chose to study the metal concentrations in adult w orker bees as these are considered to provide more sensitive, reliable and up-to-date information about exposure of bees to metals in the environment than metal concentrations in pollen, honey and larvae (Bromenshenk et al, 1985;Fakhimzadeh & Lodenius, 2000;Jones, 1987;Mihaly Cozmuta et al, 2012;Porrini et al, 2003 b ;Veleminsky et al, 1990). We report here the results for the heavy metals Cd, Pb and V. The heavy metals As, Cr, Mn, and Ni are not included, because these metals either occur in relatively high natural concentrations in bee food sources such as pollen (Lambers & Chapin, 1998), or occur in commonly used components of beehives ).…”
Section: Introductionmentioning
confidence: 99%